A randomized, controlled, crossover study in patients with mild and moderate asthma undergoing treatment with traditional Chinese acupuncture - Pai, Hong Jin (2015)
OBJECTIVES:This study sought to verify the effects of acupuncture as an adjuvant treatment for the control of asthma.METHODS:This was a randomized, controlled, crossover trial conducted at the Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo. A total of 74 patients with mild/moderate, persistent asthma were randomized into two therapeutic groups: Group A - 31 patients underwent 10 real weekly acupuncture sessions, followed by a 3-week washout period and 10 sham weekly acupuncture sessions; and Group B - 43 patients underwent 10 sham weekly acupuncture sessions, followed by a 3-week washout period and 10 real weekly acupuncture sessions. Patients used short- and long-acting β-2 agonists and inhaled corticosteroids when necessary. Prior to treatment and after each period of 10 treatment sessions, the patients were evaluated for spirometry, induced sputum cell count, exhaled nitric oxide (NO) and with the Short Form 36 (SF-36) and Questionnaire on Quality of Life-Asthma (QQLA) questionnaires. Daily peak flow and symptom diaries were registered. The level of significance adopted was 5% (α=0.05).RESULTS:In Group B, after real acupuncture, there was a decrease in eosinophils (p=0.035) and neutrophils (p=0.047), an increase in macrophages (p=0.001) and an improvement in peak flow (p=0.01). After sham acupuncture treatment, patients experienced less coughing (p=0.037), wheezing (p=0.013) and dyspnea (p=0.014); similarly, after real acupuncture, patients reported less coughing (p=0.040), wheezing (p=0.012), dyspnea (p